Distributed Leadership Matters : Perspectives, Practicalities, and Potential. - Harris, Alma (SAGE Publications, 2013)
The benefits of distributed leadership are yours with this research-based change process. Distributed leadership-engaging the many rather than the few in school improvement-has long been a promising theory. It's time to make it a reality. This book shows why harnessing educators' collective expertise leads to better student outcomes, and details the collaborative processes to make distributed leadership happen. Insights include: How to translate the research on distributed leadership into tangible results for your school Methods for building the social capital necessary for sustainabl.